Photoinduced cleavage of plasmid DNA in the presence of pterin - Llorente, Carlos Luis (2000)
The photoinduced cleavage of plasmid DNA by UV-A light in the presence of pterin was investigated. Electrophoretic analysis of the irradiated plasmid pUC18 in the presence of pterin showed that UV light of 350 nm induced the transformation of a significant proportion of the supercoiled plasmid to its relaxed form. A minor proportion of plasmid forms are also converted to the linear plasmid isomer at the longer irradiation times. All these transformations during irradiation can be observed in the absorption spectrum of DNA as function of time. Such spectral modifications correlated with the extent and the kinetics of plasmid relaxation, but not with the appearance of the linear plasmid. None of these changes were operative without the irradiation with UV-A light. Control experiments with pterin or plasmid DNA irradiated separately, showed no photochemical changes. Results taken together suggest that the observed changes in the supercoiled plasmid as well as the spectral modifications both derive from the generation of single-strand break in the DNA.